1981
DOI: 10.1021/bi00511a044
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of allosteric activation of glycogen phosphorylase probed by the reactivity of essential arginine residues. Identification of an arginine residue involved in the binding of glucose 1-phosphate

Abstract: We have previously reported the physicochemical and kinetic properties of glycogen phosphorylase modified by arginine-specific reagent under different conditions [Dreyfus, M., Vandenbunder, B., & Buc, H. (1980) Biochemistry 19, 3634-3642]. The properties of the modified enzyme depend upon the conformation adopted by the enzyme during the modification reaction. In this paper, we report the localization of the crucial modified arginine residues on the primary structure. The chymotryptic peptide extending from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The latter two amino acids may react with phenylglyoxal under some conditions (Takahashi, 1968(Takahashi, , 1977a). The partial regeneration of arginine during acid hydrolysis has been reported (Vandenbunder et al, 1981). The sulfhydryl content determined with 5,5'-dithiobis(2-nitrobenzoic acid) in the presence of 0.1% sodium dodecyl sulfate (Ellman, 1959) is unchanged by modification (data not shown).…”
Section: Competition Between Phenylglyoxal and L-serine Formentioning
confidence: 76%
See 1 more Smart Citation
“…The latter two amino acids may react with phenylglyoxal under some conditions (Takahashi, 1968(Takahashi, , 1977a). The partial regeneration of arginine during acid hydrolysis has been reported (Vandenbunder et al, 1981). The sulfhydryl content determined with 5,5'-dithiobis(2-nitrobenzoic acid) in the presence of 0.1% sodium dodecyl sulfate (Ellman, 1959) is unchanged by modification (data not shown).…”
Section: Competition Between Phenylglyoxal and L-serine Formentioning
confidence: 76%
“…The functional arginyl residue has been located in the sequence of only two enzymes which contain pyridoxal phosphate: glycogen phosphorylase (Vandenbunder et al, 1981) and aspartate aminotransferase (Sandmeier & Christen, 1982).…”
mentioning
confidence: 99%
“…13 (Riordan, 1979) . In some studies, however, a 1 :1 stoichiometry has been reported (Borders and Riordan, 1975 ;Werber et al, 1975 ;Kazarinoff and Snell, 1976 ;Philips et al, 1979 ;Vandenbunder et al, 1981) . These 1 :1 stoichiometries have usually been found under conditions of low phenylglyoxal concentration (Borders and Riordan, 1975) or in the presence of borate buffer (Werber et al, 1975 ;Kazarinoff and Snell, 1976 ;Vandenbunder et al, 1981) .…”
Section: Reaction Ofarginyl Residues With Phenylglyoxalmentioning
confidence: 97%
“…In some studies, however, a 1 :1 stoichiometry has been reported (Borders and Riordan, 1975 ;Werber et al, 1975 ;Kazarinoff and Snell, 1976 ;Philips et al, 1979 ;Vandenbunder et al, 1981) . These 1 :1 stoichiometries have usually been found under conditions of low phenylglyoxal concentration (Borders and Riordan, 1975) or in the presence of borate buffer (Werber et al, 1975 ;Kazarinoff and Snell, 1976 ;Vandenbunder et al, 1981) . Borate can presumably complex the cis-diol of Selective Modification ofthe Anion Transport System Scheme for the reaction of the guanidine free-base of an arginyl residue with phenylglyoxal.…”
Section: Reaction Ofarginyl Residues With Phenylglyoxalmentioning
confidence: 99%
See 1 more Smart Citation